2022
DOI: 10.3390/jfb13040214
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinting Technology and Hydrogels Used in the Process

Abstract: 3D bioprinting has gained visibility in regenerative medicine and tissue engineering due to its applicability. Over time, this technology has been optimized and adapted to ensure a better printability of bioinks and biomaterial inks, contributing to developing structures that mimic human anatomy. Therefore, cross-linked polymeric materials, such as hydrogels, have been highly targeted for the elaboration of bioinks, as they guarantee cell proliferation and adhesion. Thus, this short review offers a brief evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…However, the delicate nature of the hydrogel results in fragile and mechanically unstable constructs. [143] Furthermore, cells in a bio- License. [142] Copyright 2022, The Authors, published by SAGE Publications.…”
Section: Construction Of Biomimetic Organ/tissue Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the delicate nature of the hydrogel results in fragile and mechanically unstable constructs. [143] Furthermore, cells in a bio- License. [142] Copyright 2022, The Authors, published by SAGE Publications.…”
Section: Construction Of Biomimetic Organ/tissue Constructmentioning
confidence: 99%
“…However, the delicate nature of the hydrogel results in fragile and mechanically unstable constructs. [ 143 ] Furthermore, cells in a bioprinted construct are usually embedded in crosslinked hydrogel, therefore a diffusion limit, which is ≈100–200 µm for oxygen in hydrogels resulting in insufficient cellular access to nutrients and oxygen, is one of the challenges in the bioprinted construct. [ 19 ]…”
Section: Application Of Nfm Fabrication Techniques For Construction O...mentioning
confidence: 99%
“…However, pure alginate lacks functional groups that stimulate cell adhesion and proliferation. It also has low mechanical properties [82,96]. Alternative studies have shown that combining alginate with other biomaterials-for example, collagen and gelatin-revealed promising results, mainly improving cell adhesion and proliferation.…”
Section: Biomaterialsmentioning
confidence: 99%
“…The most relevant and widely used 3D bioprinting approaches for the engineering of 3D constructs include inkjet-based (Angelopoulos et al, 2020;Prabhakaran et al, 2022), laser-assisted (Heinrich et al, 2019), and extrusion-based bioprinting (Jeong et al, 2020). The specifics of these 3D bioprinting technologies are beyond the scope of this review and can be found in details elsewhere (Chameettachal et al, 2019;Cidonio et al, 2019;Scognamiglio et al, 2020;Lima et al, 2022;Karvinen and Kellomäki, 2023;Sabzevari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%